Validation of the Measurement Model (Learning And Facilitation-Laf) of Role-Performance Model Scale (RPMS) for Mandarin Lecturers at Malaysian Local Universities - Yee Chin Yip; Nurhasma Muhamad Saad; Wan Moharani Mohammad; Nurul Ain Chua Abdullah; Ng Siew Yin (Penerbit Universiti Islam Melaka, 2025)
Non-Indexed Publication